2019
DOI: 10.1155/2019/8174986
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte Colony Stimulating Factor (G-CSF) Induced Splenic Infarction in Breast Cancer Patient Treated with Dose-Dense Chemotherapy Regimen

Abstract: Introduction. Granulocyte colony-stimulating factor (G-CSF) is commonly used for prevention and treatment of febrile neutropenia among solid tumor patients. It is considered an effective and relatively safe supportive care medication; however, it can cause rare and serious side effects such as spleen rupture or infarction. Case Presentation. We are reporting a case of a 27-year-old female with breast cancer who has been treated with dose-dense chemotherapy and received colony-stimulating factor as primary prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…According to Khinji and ------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------2018 2019 2020 - -------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------- Linenberger (14), of 2,992 cases of adverse events linked to rhG-CSF preparations, 15 (0.5%) included splenomegaly; in addition, Aubrey-Bassler and Sowers (15) reported that, of 613 cases of splenic rupture, 10 (1.6%) were associated with rhG-CSF preparations. There are several case reports of splenic rupture and infarction when rhG-CSF preparations were administered to patients with cancer for the purpose of treating or preventing myelosuppression by chemotherapy and to healthy donors prior to stem cell transplantation (16)(17)(18)(19). However, the PubMed search revealed no reports of splenomegaly hypothetically associated with G-CSF produced by solid tumors, other than the present case and a previously reported case by de Wolff et al (20).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…According to Khinji and ------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------2018 2019 2020 - -------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------- Linenberger (14), of 2,992 cases of adverse events linked to rhG-CSF preparations, 15 (0.5%) included splenomegaly; in addition, Aubrey-Bassler and Sowers (15) reported that, of 613 cases of splenic rupture, 10 (1.6%) were associated with rhG-CSF preparations. There are several case reports of splenic rupture and infarction when rhG-CSF preparations were administered to patients with cancer for the purpose of treating or preventing myelosuppression by chemotherapy and to healthy donors prior to stem cell transplantation (16)(17)(18)(19). However, the PubMed search revealed no reports of splenomegaly hypothetically associated with G-CSF produced by solid tumors, other than the present case and a previously reported case by de Wolff et al (20).…”
Section: Discussionmentioning
confidence: 55%
“…According to Khinji and Linenberger ( 14 ), of 2,992 cases of adverse events linked to rhG-CSF preparations, 15 (0.5%) included splenomegaly; in addition, Aubrey-Bassler and Sowers ( 15 ) reported that, of 613 cases of splenic rupture, 10 (1.6%) were associated with rhG-CSF preparations. There are several case reports of splenic rupture and infarction when rhG-CSF preparations were administered to patients with cancer for the purpose of treating or preventing myelosuppression by chemotherapy and to healthy donors prior to stem cell transplantation ( 16-19 ). However, the PubMed search revealed no reports of splenomegaly hypothetically associated with G-CSF produced by solid tumors, other than the present case and a previously reported case by de Wolff et al ( 20 ).…”
Section: Discussionmentioning
confidence: 99%